Pengaturan Integrasi Kearifan Lokal dalam Penataan Lingkungan di Provinsi Bali - A.A. Kt. Sudiana (Jurnal Hukum Saraswati (JHS), 2025)
Building a pattern of environmental law enforcement system with the ADS approach based on local wisdom is an effort to integrate the cultural order with the structural order in regulating environmental protection and management. Economic development policies in Bali must not ignore local wisdom which has an important role as an environmental order, such as the Tri Hita Karana philosophy (regulating three harmonious relationships, namely; the relationship between humans and God, the relationship between humans and humans, and the relationship between humans and the natural environment). The three elements of the Hindu religious framework are the soul of Balinese culture (as aspects of local wisdom), among others, emphasizing that the acculturation between local Balinese culture and Hindu religion and culture gave birth to traditional Bali. With the application of customary sanctions in awig-awig and legal sanctions from the state which are carried out in an integrated, firm, and consistent manner. Based on various forms of local wisdom, namely; Desa Pakraman, Awig-Awig, Tri Hita Karana Philosophy, Holy Places (Tura), Lelipi Selahan Bukit/Wong Samar Myth, Wana Kertib/Tumpek Wariga Ceremony, and Animism Beliefs, which are used as tools for Environmental Management in Bali Province